Living in Limbo : Conflict-Induced Displacement in Europe and Central Asia. - Holtzman, Steven B., 1959- (World Bank e-Library., 2004)
"The conflicts in Europe and the former Soviet Union of the 1990s left in their wake nearly 10 million refugees and internally displaced persons. Even where peace treaties or ceasefire have brought an end to open conflict, about half of those originally displaced remain caught between two worlds. They cannot go home. At the same time, they face a range of difficulties in settling where they are." "Long-term, conflict-induced displacement creates both conceptual and operational challenges for development agencies concerned with poverty reduction. Living in Limbo analyzes the special nature of displacement-induced vulnerability along several dimensions, including material well-being, employment, shelter, and human and social capital. The study draws on the authors' field work as well as extensive review of surveys, studies, and poverty assessments in 13 countries."